Improving efficiency in hospital pharmacy systems: the case for color-coded zones for rapidly dispensed medications - Ammar Abdulrahman Jairoun; Sabaa Saleh Al-Hemyari; Moyad Shahwan; Faris El-Dahiyat; Abeer M. Al-Ghananeem (Journal of Pharmaceutical Policy and Practice)
Colour-coded zones for rapidly dispensed medications are a simple, yet game-changing solution to improve the efficiency and safety of hospital pharmacy systems. This approach integrates visual ergonomics, staff training, and technology in solving some of the most common challenges in medication retrieval and general healthcare delivery. This evidence-based system will go a long way in helping hospitals meet the ever-increasing demands. While colour-coded zoning schemes offer a practical and cost-effective way to enhance pharmacy efficiency and medication safety, their effectiveness depends on careful implementation, standardisation, and integration with digital tools. Although highly digitalised healthcare systems may rely more on automated inventory tracking and barcode verification, colour coding remains a valuable supplementary measure, particularly in fast-paced clinical environments. For resource-limited healthcare facilities, colour-coded zoning serves as an essential safety mechanism where advanced IT solutions may not be feasible. However, standardisation challenges, risks of over-reliance, and accessibility concerns for colour-blind individuals must be addressed to maximise effectiveness. Ultimately, an optimal pharmacy management system may involve a hybrid approach that integrates both visual and digital verification methods, ensuring both efficiency and patient safety across diverse healthcare settings.